2016
DOI: 10.4014/jmb.1601.01043
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Yield of Lactic Acid for Antimicrobial Characterization in Cephalosporin-Resistant Lactobacillus by the Co-Expression of the Phosphofructokinase and Glucokinase

Abstract: Lactobacilli are universally recognized as probiotics that are widely used in the adjuvant treatment of inflammatory diseases, such as vaginitis and enteritis. With the overuse of antibiotics in recent years, the lactobacilli in the human body are killed, which could disrupt the microecological balance in the human body and affect health adversely. In this work, cephalosporin-resistant Lactobacillus casei RL20 was obtained successfully from the feces of healthy volunteers, which possessed a stable genetic set.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previous studies showed that increasing the activity of PFK can improve d ‐lactic acid productivity in Sporolactobacillus inulinus , [ 38 ] and an engineered Lactobacillus casei strain with co‐expression of PFK and glucokinase also showed increasing activities of PFK and glucokinase, resulting in enhanced lactic acid production. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that increasing the activity of PFK can improve d ‐lactic acid productivity in Sporolactobacillus inulinus , [ 38 ] and an engineered Lactobacillus casei strain with co‐expression of PFK and glucokinase also showed increasing activities of PFK and glucokinase, resulting in enhanced lactic acid production. [ 39 ]…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that increasing the activity of PFK can improve D-lactic acid productivity in Sporolactobacillus inulinus, [38] and an engineered Lactobacillus casei strain with coexpression of PFK and glucokinase also showed increasing activities of PFK and glucokinase, resulting in enhanced lactic acid production. [39] Interestingly, based on the result of gene expression profiles at the 4 h fermentation period (Figure S1 and Table S1), L-cysteine addition boosted gene expression value involving in fatty acid degradation. The results indicated that L-cysteine addition accelerated the growth and metabolism of B. coagulans at the early fermentation stage (4 h) than that noted in non-supplemented L-cysteine group.…”
Section: Coagulansmentioning
confidence: 96%
“…Undissociated short-chain fatty acids are lipophilic and can bind with phospholipids and LPS on the bacteria's cell membrane, lowering the stability of the bacterial membrane. Undissociated organic acids can even enter into the cytoplasm through the phospholipid bilayer of microorganisms and release H + to alter microorganisms' original pH environment, resulting in a decrease in enzymatic activity and metabolic disorder of other bacteria (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…This case demonstrates the importance of early recognition and suspicion of Lactobacillus in patients who do not respond to initial empiric antibiotic therapy for SBP. This becomes furthermore important since Lactobacillus can be gram variable, and they can be intrinsically resistant to most cephalosporins and vancomycin [11].…”
Section: Discussionmentioning
confidence: 99%